The Effectiveness of Revenue Collection Methods and Its Impact on the Quality of Services Delivered in Mukono District Local Government - Sharon Nabakeni (Uganda Christian University, 2023)
The study delves into the relationship between local revenue collection methods and service delivery within the context of Mukono district local government. A total of 44 questionnaires were distributed to staff members and community members, achieving a commendable response rate of 91.32%. The respondents' background information were analyzed, revealing a predominantly youthful population aged 18-25 years, a majority of females, and a prevalence of individuals with degree-level education. Moreover, a significant portion of the respondents was indirectly engaged in revenue collection. The study focused on the dependent variable, as services delivered conceptualized as the quality of services delivered by Mukono local government. Findings indicated that respondents were dissatisfied with the current state of services and that revenue collection did not significantly contribute to service improvement. In examining revenue collection methods, the study identified cash payments and third-party processors as prevalent approaches. Additionally, the acceptance of credit card payments and online methods for revenue collection was reported. Incentives for prompt payment and tax compliance were also in use. A multiple linear regression analysis was performed to assess the impact of education level, revenue collection methods, and revenue collection challenges on service delivery. The results indicated that only revenue collection methods and revenue collection challenges significantly influenced service delivery, while education level did not have a significant impact. The study further explored the challenges faced by the revenue authority in collecting taxes, revealing inefficiencies in the revenue collection process, challenges related to tax evasion and non-compliance, a lack of transparency, ethical concerns, and a low level of tax compliance.In conclusion, this study underscores the importance of revenue collection methods and addressing revenue collection challenges to enhance service delivery in Mukono local government. It recommends measures such as expanding the tax base, increased sensitization, timely accountability, transparency, and identifying additional revenue sources. These findings provide valuable insights for policymakers and practitioners in local government administration. For future research, it is suggested to explore revenue generation, collection, and allocation across different local governments, investigate various sources of local revenue in Mukono, and explore strategies for expanding the local revenue base.
THis is a dissertation.